Community Pharmacy Service under the National Health Insurance in Australia - Upakdee, Nilawan; Dhippayom, Teerapon (Journal of Health Science of Thailand, 2017)
Community pharmacy is deemed as one of the main primary healthcare units due to the convenience in accessing the services. However, community pharmacies in Thailand have not yet been encompassed in the formal health care benefit schemes. A review of service arrangement in countries that support community pharmacy services will help directing the development of community pharmacy services in Thailand. A Community Pharmacy Agreement in Australia was achieved through negotiation between the Pharmacy Guild of Australia and the Federal Government, which has been guided by research evidences and the Guild’s roadmap. Programs and services that received financial support in the current Fifth Agreement are medication management programs, rural support programs, Aboriginal and Torres Strait Islander programs, pharmacy practice incentive and accreditation, research development, and medication continuance. The following are key findings learnt from Australia which can be adapted to support the development of community pharmacy services in Thailand: a dedicated organization should be apportioned to responsible for the development of the profession roadmap and the negotiation with the government to achieve the Pharmacy Agreement; a strategic plan to support related research should be established to generate evidence to back-up the negotiation with the government; and a financial support should be allocated as part of a service accreditation and as an incentive to pharmacies that provide services that improve the quality use of medicine.